PENGARUH MODEL PEMBELAJARAN NUMBERED HEAD TOGETHER (NHT) BERBANTUAN MEDIA AUDIOVISUAL TERHADAP HASIL BELAJAR SISWA PADA MATERI BUDAYA DAERAH INDONESIA KELAS V SD NEGERI 45 PANGKALPINANG - Mona Hisya; M. Iqbal Arrosyad; Yurdayanti (STKIP Subang, 2026)
The main issue underlying this study is the low learning outcomes of students regarding Pancasila values, as many are still below the minimum passing grade (KKM), with only 11 out of 25 students achieving the KKM. Another factor is the lack of student participation during presentations. This study aims to understand the impact of the Numbered Heads Together (NHT) method using audiovisual aids on student learning outcomes on the topic of Indonesian regional culture in Grade V of SD Negeri 45 Pangkalpinang. A quantitative approach was used with a pre-experimental design and a one-group pretest-posttest design. This study included 14 fifth-grade students at SD Negeri 45 Pangkalpinang, using a saturated sampling technique. Data were obtained from a test consisting of five essay questions. Data were obtained from learning outcome tests and analyzed using the Shapiro Wilk normality test and the Paired Sample T-Test hypothesis test. The study showed that the average pretest score was 42.14 with a minimum score of 25 and a maximum score of 55, while the average posttest score was 70.71 with a minimum score of 50 and a maximum score of 95. It can be concluded that the Numbered Heads Together (NHT) method using audiovisual aids had an impact on the learning achievement of fifth-grade students at SD Negeri 45 Pangkalpinang in the subject of Indonesian regional culture.